Incidence of agenesis of palmaris longus in the Andhra population of India - K. Devi Sankar; P. Sharmila Bhanu; Susan P. John (Indian Journal of Plastic Surgery)
Background: The knowledge of Palmaris longus (PL) is a growing interest for its wide role in reconstructive plastic surgeries as a donor tendon for transfer or transplant. The prevalence of the PL agenesis has been well-documented by many authors in different ethnic groups or populations. Many conventional tests for determining the presence of the PL has been described, but lamentably there are many discrepancies in confirming its presence or absence. Slight modifications of the prevailing methods can still give authenticate results. Aim: This prospective study was conducted to determine the incidence of unilateral and bilateral agenesis of PL and its association with sex and side of the limb in the Andhra population of India. Materials and Methods: A total of 942 subjects of both sexes belonging to 18-23 years were used to access the PL using various tendon examination techniques including our modified Schaeffer's test. The data collected were analyzed by Pearsons χ2test using SPSS software. Results: Overall agenesis of muscle in both sexes was 264 (28.0%), out of which 40.2% was seen in females and 14.7% in males with the ratio of 3:1. The unilateral agenesis was seen in 70.5% and bilateral agenesis in 29.5% subjects. The left side agenesis was seen in 51.6% and right side in 48.4% subjects. Conclusions: The prevalence of bilateral and unilateral agenesis was more common on left side with a greater likelihood in the female subjects. The proposed technique could bring better results in all subjects and can be implemented in manual examination of PL.